Unearthed Treasures by Unlocking the Secrets of Forgotten Cash through Dynamic Cash Flow Analysis - Renaldo, Nicholas; Sudarno, Sudarno; Hughes, Amy; Smith, Harry; Schmidt, Matthias (First Ciera Publisher, 2024)
Cash flow is an important aspect of company finances which reflects the company's financial health and ability to fulfill its financial obligations. Cash flow statements allow stakeholders to understand how cash flows are generated and used in a given period. This research aims to gain an in-depth understanding of cash flow management, financial innovation, risk management, and modern business practices. Through a qualitative approach with literature studies, this research explains various aspects related to cash flow, starting from definitions, classifications, and problems that may occur, to the analysis techniques used. There are three main categories in the cash flow report, namely operating, investing, and financing activities. Cash flow problems can occur in the form of a deficit, break-even, or surplus. Cash flow analysis includes various ratios that measure a company's financial performance, such as operating cash flow/net sales, free cash flow, and other ratios. The results and discussion highlight the cash flow analysis techniques used, such as the calculation of operating cash flow/net sales and free cash flow, as well as various ratios that measure a company's financial performance. This research concludes that cash flow analysis is an important key in understanding company finances and making better strategic decisions. Cash flow statements help identify potential financial problems and ensure the long-term continuity of a company's operations. As suggestions for future research, this study suggests exploring the impact of technology in cash flow management, the influence of financial innovation on cash flow, risk management strategies, dividend policies, best practices in cash flow management, comparison of methods for preparing cash flow reports, the influence of tax policy, and the impact of CSR on cash flow.